Harris Surabaya Children's Language Variations in Storytelling Activities : Socio - linguistic Pragma - Akhiruddin, Harris Rizki; Laksono, Kisyani; Savitri, Agusniar Dian (VALUE: Journal of Business Studies, 2024)
This research aims to investigate the language variations found in Surabaya children's storytelling activities using a pragmasocolinguistic approach. Through participant observation and text analysis of stories told by children, this research explores how Surabaya children use their language in the context of storytelling activities. Research findings show that Surabaya children present rich variations in the use of vocabulary, grammar, and language style, which are influenced by social and contextual factors. Surabaya children tend to use words that are familiar to their daily experiences, and choose sentence structures that suit the situation and audience. External factors such as the influence of mass media are also visible in children's language use. This research provides in-depth insight into how Surabaya children use their language in storytelling activities, as well as the implications of these findings in the context of children's education and language development. In conclusion, understanding the language variations of Surabaya children in storytelling can make an important contribution to the development of effective teaching strategies and the enrichment of local culture .. Keywords: Language variations, Surabaya children, storytelling, Pragmasocolinguistics